2017
DOI: 10.3414/me16-05-0001
|View full text |Cite
|
Sign up to set email alerts
|

Representation of People’s Decisions in Health Information Systems

Abstract: SummaryObjectivesIn this study, we aimed: 1) to conceptualize the theoretical challenges facing health information systems (HIS) to represent patients' decisions about health and medical treatments in everyday life; 2) to suggest approaches for modeling these processes.MethodsThe conceptualization of the theoretical and methodological challenges was discussed in 2015 during a series of interdisciplinary meetings attended by health informatics staff, epidemiologists and health professionals working in quality m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…Recognized non-valid concepts block the input of that kind of data in the system and improve the overall quality. We are still working on enriching thesaurus descriptions and adding social determinants of health, social activities for promoting and preventing health, information on behavioral changes and people decisions and preferences 37 , familiar and other social relationships that are important for health, social assets, and relevant genetic information.…”
Section: The Hospital Italiano De Buenos Aires: Terminology Services mentioning
confidence: 99%
“…Recognized non-valid concepts block the input of that kind of data in the system and improve the overall quality. We are still working on enriching thesaurus descriptions and adding social determinants of health, social activities for promoting and preventing health, information on behavioral changes and people decisions and preferences 37 , familiar and other social relationships that are important for health, social assets, and relevant genetic information.…”
Section: The Hospital Italiano De Buenos Aires: Terminology Services mentioning
confidence: 99%
“…The stated objectives of this study [ 1 ] was to: conceptualize the theoretical challenges facing health information systems (HIS) to represent patients’ decisions about health and medical treatments in everyday life; and to suggest approaches for modeling these processes. After making a good analysis of the literature the authors confirmed the need and then the aim of this study which is “to conceptualize patient decisions about health care and the treatment of chronic diseases under new theoretical frameworks”.…”
Section: Comment By N Al-shorbajimentioning
confidence: 99%
“…De Quiros, Dawidowski and Figar’s paper entitled the “Representation of People’s Decisions in Health Information Systems: A Complementary Approach for Understanding Health Care Systems and Population Health” [ 1 ] outlines a new and important lens through which we as health informatics researchers and health information technology professionals need to view the citizens, families and communities in our country and globally. Historically, health information systems (HIS) were designed and used by health professionals (i.e.…”
Section: Comment By E Boryckimentioning
confidence: 99%
See 1 more Smart Citation
“…De Quiros and colleagues [ 1 ] are curious about the ways that health technology, specifically health information systems (HIS) might 1) create a context that makes healthy behaviors more intuitive, appealing, and facile; and 2) address illness from the biopsychosocial framework [ 2 ], measuring and accounting for the psychological, sociocultural, and environmental factors that affect health. Technology can be used to create social constructs to optimize health.…”
mentioning
confidence: 99%